2008
DOI: 10.1002/pc.20473
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the various coupling agents on the mechanical and physical properties of thermoplastic‐bagasse fiber composites

Abstract: Various types of bonding agents have been tried with blends of bagasse fibers and some thermoplastics such as low‐density polyethylene (LDPE), high‐density polyethylene (HDPE), polystyrene (PS), polypropylene (PP), and polyvinyl chloride (PVC). These bonding agents are, namely, pentaerythritol tetracrylate (PETA), 1,6 hexandiol diacrylate (HDA), and dicumyl peroxide (DCP). In addition, a traditional coupling agents 3‐aminopropyltrimethoxy silane (AMPS) and di‐aminopropyltrimetoxy silane (DAMPS) were included f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Recently, studies have reported the use of sugarcane bagasse fibers as filler in thermoplastic composite. The majority of these works developed plastics with distinct mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have reported the use of sugarcane bagasse fibers as filler in thermoplastic composite. The majority of these works developed plastics with distinct mechanical properties .…”
Section: Introductionmentioning
confidence: 99%
“…Maleic anhydride treated rubber wood fiber reinforced polyolefin composites was developed and characterized by Tasdemir et al [28]. Bagasse fiber treated with silane and dicumyl peroxide was found to improve compatibility with LDPE as reported by Yourself et al [29]. Diminished size of phase boundaries was observed for ionomer compatibilized wood/LDPE composites as observed by Sedlackova et al [30].…”
Section: Introductionmentioning
confidence: 99%
“…The increase of mechanical properties was due to improved adhesion between the fiber and matrix, which was confirmed by the increase of ∆E in stress relaxation tests. Previous literature also showed that a high compatibility at interfaces leads to better stress transfer between the two components and the improvement of mechanical and physical properties of the materials (Youssef et al 2008). It was conclusively demonstrated that the combination of PEG and heat treatment could alleviate the increasing stress relaxation rate and the decreasing strength caused by PEG impregnation, especially in the case of low-concentration PEG treatment.…”
Section: Discussionmentioning
confidence: 57%